ADAPTATION POTENTIAL STRUCTURE IN GIFTED ADOLESCENTS - O. O. Andronnikova; Yu. M. Perevozkina; N. V. Dmitrieva; N. A. Shchukina (Вестник Кемеровского государственного университета, 2017)
The article reflects the main approaches to the problem of adaptive potential. It featured the essence and content of the adaptive potential of modern psychology and analyzes the structural components of the adaptation potential, including neuropsychic stability, self-esteem, communicativity, psychic regulation, etc. The paper describes the features of adaptation of gifted adolescents and the structure of the adaptive potential, which is represented as a multi-level system. It is suggested that the structure of the adaptive potential of gifted adolescents includes emotional, reflexive, volitional and behavioral components. The test subjects were gifted adolescents aged 12–15, studying in specialized classes (engineering). The group included 56 people, 26 boys and 20 girls. The article describes the data of factor analysis by the method of principal components with rotation "varimax normalized". The analysis has demonstrated that the structure of the adaptive potential of gifted adolescents includes five factors explaining 57.02 % of the total variability. The results of factor analysis allow the authors to come to the conclusion that the adaptive potential of gifted adolescents includes five components: 1 and 2 components reflect the emotional component, i.e. the ability to understand how to express your feelings and feelings of others; 3 – reflexive component, i.e. ability to internal analysis of their actions and actions; 4 – behavioral component, i.e. propensity to react in a certain way to a particular situation; 5 – strong-willed component, i.e.  ability to regulate one’s emotional behavior in unusual situations.